(untitled) (Ustozlar uchun, 2026)
This thesis analyzes innovative methods in pedagogy, translation, and foreign language teaching in modern education. It focuses on active learning, problem-based learning, and technology-assisted instruction. These approaches contribute to the development of students’ communicative competence, critical thinking, and learner autonomy.